Sebuah Kajian Historis: Periodesasi Dan Tartib Mushafi Ayat-Ayat Al-Quran - Majid, Abdul; Sugitanata, Arif (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2021)
The existence of the Koran cannot be separated from the history of the beginning of revelation, this shows that the Koran came back and the reason for that verse was revealed, because the Koran is an eternal and appreciative miracle that comes out of its relevance in facing all changes. Al-Quran is the holy book contained in the main teachings for human life, both from the perspective of economy, education, government, health and so on. These instructions are the basis for adherents to always hold fast in carrying out all activities for the happiness of life in this world and in the hereafter. This paper tries to review the period of Makkiyah and Madaniyah and explains the tartib which is the basis for the compilation of the Koran, so that it can be seen that the purpose of the Qur'anic verse which was passed down gradually was to provide for its adherents and as a differentiator from books that also the arrangement of verses and letters in the Koran is more tauqifi based on the Prophet's instructions in accordance with Allah's revelation because the Koran is a miracle of the Prophet Muhammad which contains universal values ​​and is interrelated as a whole in one unity.